Phenotypic adaptation of Mycobacterium tuberculosis to host-associated stressors that induce persister formation - Parbhoo, Trisha; Mouton, Jacoba M.; Sampson, Samantha L. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium tuberculosis exhibits a remarkable ability to interfere with the host antimicrobial response. The pathogen exploits elaborate strategies to cope with diverse host-induced stressors by modulating its metabolism and physiological state to prolong survival and promote persistence. Elucidating the adaptive strategies that M. tuberculosis employs during infection to enhance persistence is crucial to understanding how varying physiological states may differentially drive disease progression for effective management of these populations. To improve our understanding of the phenotypic adaptation of M. tuberculosis, we review the adaptive strategies employed by M. tuberculosis to sense and coordinate a physiological response following exposure to various host-associated stressors. We further highlight the use of animal models that can be exploited to replicate and investigate different aspects of the human response to infection, to elucidate the impact of the host environment and bacterial adaptive strategies contributing to the recalcitrance of infection.